PENGARUH PENGETAHUAN DAN MOTIVASI KERJA KADER POSYANDUTERHADAP KUALITAS PELAYANAN KESEHATAN BALITA DAN IBU HAMIL DI POSYANDU DESA TEMON KECAMATAN BATURETNO WONOGIRI - Ikhwan Zaeni; Fajar Alam Putra; Farida Nugrahani (Universitas Sahid Surakarta, 2015)
Background: Posyandu program implemented for the benefit of society, it is expected that the community itself is the active form, organize, exploit and develop best IHC. Continuity IHC depends on the participation of the community itself. The organizers of IHC are cadres and the PKK from the village (Budioro, 2002). Based on the above description, it can be formulated: